On the nature of phase separation of polymer solutions at high extension rates. Issue 8 (1st February 2015) - Semakov, Alexander V.; Kulichikhin, Valery G.; Tereshin, Aleksei K.; Antonov, Sergei V.; Malkin, Alexander Ya.
ABSTRACT Experiments with stretching moderately concentrated polymer solutions have been carried out. Model experiments were carried out for poly(acrylonitrile) solutions in dimethyl siloxane. Just the choice of concentrated solutions allowed for a clear demonstration of a demixing effect with the formation of two separate phases—an oriented polymer fiber and solvent drops sitting on its surface. An original experimental device for following all subsequent stages in the demixing process was built. It combined two light beams, one transverse to the fiber and a second directed along (inside) the fiber, the latter played the role of an optical line. This gives a unique opportunity to observe processes occurring inside a fiber. The process of demixing starts from the volume phase separation across the whole cross section of a fiber at some critical deformation and the propagation of the front of demixing along the fiber. Then a solvent cylindrical skin appears which transforms into a system of separate droplets. New experimental data are discussed based on a comparison of the current different points of view on the phenomenon of deformation‐induced phase separation: thermodynamic shift of the equilibrium phase transition temperature, growth of stress‐induced concentration fluctuations in two‐component fluids, and mechanically pressing a solvent out from a polymer network. The general belief is that a rather specific (so‐called "beads‐on‐a‐string") structure of a filament is realized in stretching dilute solutions: beads of a polymer solution connected by oriented polymer bridges forming a single object. The situation in stretching moderately concentrated solutions appears quite different: real phase separation was observed. So, the alternative phenomenon to the formation of the "beads‐on‐a‐string" structure has been experimentally proven. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 559–565